Draft genome assembly of the largemouth bass (Micropterus salmoides) - Tao Zhu; Hongmei Song; Jinxing Du; Caixia Lei; Jing Tian; Chenghui Wang; Chuanju Dong; Shengjie Li (BMC Genomic Data)
Abstract Objective Largemouth bass (Micropterus salmoides, LMB) is an important species in aquaculture, and the annual production is rapidly increasing. Genetic and breeding studies related to LMB have promising applications, and a high-quality genome assembly is essential for interpreting genetic and sequencing data. In this study, we sequenced the genome of a male LMB using the PacBio Sequel platform, high-throughput chromosome conformation capture (Hi-C), and paired-end Illumina sequencing. Additionally, Full-length transcript sequencing was performed using isoform sequencing (Iso-Seq). Following the assembly and annotation, a draft assembly for male LMB was obtained. Data description This work generated PacBio data of 164.5 Gb, Hi-C data of 113.4 Gb, Illumina data of 54.7 Gb, and Iso-Seq data of 22.8 Gb. The assembly revealed that the LMB genome has a total length of 877.7 Mb, with an N50 of 37.2 Mb, comprising 23 chromosomes and 202 scaffolds. Annotation results indicated that 32.8% of the genome consists of repetitive sequences, containing 23,952 coding genes with an average gene length of 17,328 bp.